2018
DOI: 10.1002/ejoc.201800441
|View full text |Cite
|
Sign up to set email alerts
|

Dichloro‐Substituted 1,2‐Diazabuta‐1,3‐dienes as Highly Reactive Electrophiles in the Reaction with Amines and Diamines: Efficient Synthesis of α‐Hydrazo Amidinium Salts

Abstract: The reaction of 4,4‐dichloro‐1,2‐diazabuta‐1,3‐dienes with various amines and diamines was studied. We found that in this reaction, the starting diazabutadienes behave as highly reactive electrophiles to open up a straightforward route to the corresponding amidinium salts with a hydrazone functionality in the adjacent position. The reaction was found to be very general; as a rule, all the products could be prepared in almost quantitative yields. We also demonstrated that the prepared amidinium salts could be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…All manipulations with any azides demand significant care due to safety reasons! o-Propargyloxy-substituted 4-azido-2,5-diaryl-1,2,3-triazoles were obtained according to the procedure described in this paper [27]. A 20 mL screw neck vial was charged with DMSO (10 mL) and sodium azide (5 eq.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All manipulations with any azides demand significant care due to safety reasons! o-Propargyloxy-substituted 4-azido-2,5-diaryl-1,2,3-triazoles were obtained according to the procedure described in this paper [27]. A 20 mL screw neck vial was charged with DMSO (10 mL) and sodium azide (5 eq.…”
Section: Methodsmentioning
confidence: 99%
“…These compounds can be prepared using the reaction of carbon tetrachloride witH-N-substituted hydrazones of aldehydes in the presence of CuCl as a catalyst. [26,27] Recently we demonstrated that these compounds are also interesting diazodyes [28,29]. The reaction of 4,4-dichloro-1,2-diazabuta-1,3-dienes with sodium azide has been found to open straightforward access to extremely rare 1,1-bis-azides ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Dichloro‐substituted heterodienes of this type are poorly described in the literature, and data about their reactivity are still very sparse . Due to the presence of the electron‐withdrawing aza group, 4,4‐dichloro‐1,2‐diazabuta‐1,3‐dienes are highly reactive and useful electrophiles . The next subject of our research was the reactions of dichlorodiazadienes with C‐nucleophiles, in particular, with malononitrile .…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that dichloro‐substituted heterodienes of this type are poorly described in the literature . Due to the presence of the electron‐withdrawing aza‐group, these azadienes are highly reactive and useful electrophiles . This work is devoted to study of the reactions of dichloro‐substituted 1,2‐diaza‐1,3‐dienes with malononitrile to construct pyridazine derivatives.…”
Section: Introductionmentioning
confidence: 99%